From Knowing to Understanding Student Empowerment: A Narrative Approach to Research in a Middle School - Brian R Horn (Networks: An Online Journal for Teacher Research, 2015)
This paper examines how, as a teacher researcher, I employed a narrative approach to research to better understand my 8th grade Language Arts students’ empowerment in school. Drawing on sociocultural theory, critical pedagogy and a narrative approach to teacher research, students’ voices were privileged and compared to the systemic assumptions regarding student empowerment inherent in No Child Left Behind (NCLB) policy in order to develop a stronger professional understanding of how schools empower and disempower students.